PERANAN KESENIAN REBANA WALISONGO SRAGEN DALAM STRATEGI DAKWAH KH.MA’RUF ISLAMUDDIN (THE ROLE OF SRAGEN WALISONGO TAMBOURINE ART IN KH. MA’RUF ISLAMUDDIN’S DA’WAH STRATEGY) - Pujiyanto, Tri (Candi)
Abstract Considering the result of research, it could be concluded: (1) the idea of conducting da?wah with art as well as art departed from Walisanga?s concept. KH. Ma?ruf Islamuddin proselytized using tambourine as the means of distributing Islam religion to make the proselytizing acceptable to the public. (2) The tambourine that KH. Ma?ruf Islamuddin used as Islamiyah da?wah used lyric containing the invitation to undertake amar ma?ruf nahi munkar by means of changing other?s song lyric. (3) The tambourine that KH. Ma?ruf Islamuddin used as the means of Islamic proselytizing here used a variety of others? song lyrics that had been known by many people, and then rearranged them to  be more acceptable and understandable to the listeners, but the purpose or the objective of the song played was the invitation to undertake Allah?s command and to keep away from His prohibition by means of changing the lyrics, but KH. Ma?ruf Islamuddin also composed some songs by himself. (4) The attempts the Walisongo Sragen Islam Boarding School had taken in developing tambourine art can be seen from the presence of art development activity for the santri (students of Islam Boarding School): firstly, reorganizing tambourine player; secondly, establishing recording studio; and thirdly, establishing Sragen Walisongo radio studio. Key words: Arts the tambourine Walisongo?s Sragen